Rural Community Economic Strengthening Model Based On Village-Owned Enterprises In Central Maluku Regency - Maryam Sangadji (MediaTrend, 2021)
Village-owned enterprises (BUMDes) in Indonesia, as village economic institutions can drive village potential, by the Central Maluku communities BUMDes is called as a BUMNeg which have the same meaning. BUMNeg becomes village income (Village Law, No. 6 of 2014). Objectives of the study: (1) Knowing the Role and Development of Village-Owned Enterprises that have been intervened through capital participation from the Village Fund, (2) Understanding the potential and capacity of villages constraint factors and main supporters in supporting the activities of Village-Owned Enterprises, (3) Obtaining a management model of Village-Owned Enterprises that is in accordance with the local conditions of the village community. The study used a qualitative approach. The results of the study illustrate (1) the role of BUMDes in the sample villages having different results. In Waai Villlage the existence of the BUMDes has been carried out in accordance with the functions of the BUMDes, namely carrying out economic functions. Whereas the existence of BUMDes in Tulehu Village was not carried out, village funds were only embedded in goods purchased, and only functioned socially, not functioned to generate village income. (2) Obstacles and main supporters of the BUMDes are: (a) The existence of potential natural resources, but not yet managed, (b) Potential Number of residents not managed as a business unit management market in Tulehu Village, (c) Custom institutions do not function, (d) Village funds are not managed according to their functions in Tulehu Village, in Waai village according to function, (e) Location of Waai Village is very strategic with potential villages. (3) BUMDes Strengthening Model in Tulehu village will exist through three stages: activation, implementation and development. Strengthening the BUMDes in Waai village, namely: building a network with the village’s government / king to continue to maintain trust relations and build networks with other parties as a reinforcement of BUMDes development